Potential Antioxidant and Enzyme Inhibitory Effects of Nanoliposomal Formulation Prepared from Salvia aramiensis Rech. f. Extract - Gökçe Şeker Karatoprak; Çiğdem Yücel; Fatih Göger; Eduardo Sobarzo-Sánchez; Esra Küpeli Akkol (MDPI AG, 2020)
Salvia aramiensis Rech. f. is a species that grows only in Hatay, Turkey and is used as a traditional stomachic tea. Neither the chemical composition nor the potential bioactivity of the plant has been investigated before. Antioxidant activity (1,1-Diphenyl-2-picrylhydrazyl Radical (DPPH●) and 2,2'-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS+●) radical scavenging and β-carotene/linoleic acid co-oxidation) of 70% methanol, 70% ethanol extracts, and 2% infusion obtained from S. aramiensis aerial parts were determined. The effect of 70% methanol extract on collagenase and elastase enzyme inhibition and its chemical composition via chromatographic methods (LC-MS/MS and HPLC) were analyzed. Nanoliposomes were developed with 70% methanol extract, were characterized, and were evaluated. The key parameters for the most active 70% methanol extract included the following DPPH•EC50: 28.4 µg/mL, Trolox equivalent antioxidant capacity (TEAC)/ABTS: 1.77 ± 0.09 mmol/L/Trolox. Furthermore 70% methanol extract showed more than 50% inhibition on collagenase and elastase enzymes at all the concentrations. The main component of the extract, rich in phenolic compounds, has been identified as rosmarinic acid; 83.7 µg/mL extract was released from the nanoliposomal formulation. The extract and its formulation are found to be nontoxic on the L929 fibroblast cell line. This study successfully developed a long-term antioxidant and enzyme inhibitory formulation containing S. aramiensis, which has been used safely among the public for years.